Slavery, Abstract Labour, and the Constitution of Capitalism - Lamas, Bruno (Comparativ, 2021)
Capital is a form of “abstract wealth” (Marx), socially and historically specific to modern society and based on undifferentiated combustion of human energy: “abstract labour”. The historical constitution of capitalism is the worldwide process of constituting that nexus between abstract wealth and abstract labour, effectively reducing human beings to mere carriers of bodily energy to be mobilized for the valorization of value. In this article, starting from a theoretical reflection on the historicity of three of the main categories of Marx’s critique of political economy – value, labour, and abstract labour – I intend to (i) provide a general interpretation of the historical process of constitution of capitalism between the sixteenth and nineteenth century, as the transition from a newly created world system of monetary-wealth circulation to a world system of abstract labour; (ii) reflect on the role of slavery in this process and its relationship with the constitution of the specifically modern categories of labour and labour power; and (iii) show that, despite its past and common elements, it is the essential differences between the slave commodity and the labour power commodity through the self-ownership category that will ultimately become decisive for modern struggles for social recognition and the historical constitution of capitalism itself.